2008
DOI: 10.1097/ftd.0b013e318178e2a9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lamotrigine Pharmacokinetics during Pregnancy and the Puerperium

Abstract: To assess changes in the pharmacokinetics of the anti-epileptic drug lamotrigine (LTG) during pregnancy, plasma LTG concentrations at steady-state were determined at different intervals during 11 pregnancies in 10 women with epilepsy stabilized on long-term LTG therapy. In the five pregnancies that could be assessed both during gestation and after delivery, plasma LTG concentrations increased on average by 164% (range +75 to +351%) between the last observation during pregnancy and the puerperium (P < 0.05). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This is of importance due to the fact that UGT enzymes often contribute not only to the elimination of the parent drug but also to the elimination of pharmacologically active metabolites or metabolites that are used as markers of P450 activity. For example, circulating concentrations of the antiepileptic drug lamotrigine decreased by about 50% during pregnancy (Franco et al, 2008), and the plasma concentration ratio of lamotrigine glucuronide to lamotrigine increased by about 2-fold in the second and third trimesters of pregnancy compared with postpartum (Ohman et al, 2008). Lamotrigine N-glucuronidation is predominantly mediated by UGT1A4 (Green et al, 1995), and hence, these data suggest that UGT1A4 activity is increased during pregnancy, and has important implications for seizure control in pregnant women taking lamotrigine.…”
Section: Knowledge On Enzyme-specific Changes During Pregnancymentioning
confidence: 99%
“…This is of importance due to the fact that UGT enzymes often contribute not only to the elimination of the parent drug but also to the elimination of pharmacologically active metabolites or metabolites that are used as markers of P450 activity. For example, circulating concentrations of the antiepileptic drug lamotrigine decreased by about 50% during pregnancy (Franco et al, 2008), and the plasma concentration ratio of lamotrigine glucuronide to lamotrigine increased by about 2-fold in the second and third trimesters of pregnancy compared with postpartum (Ohman et al, 2008). Lamotrigine N-glucuronidation is predominantly mediated by UGT1A4 (Green et al, 1995), and hence, these data suggest that UGT1A4 activity is increased during pregnancy, and has important implications for seizure control in pregnant women taking lamotrigine.…”
Section: Knowledge On Enzyme-specific Changes During Pregnancymentioning
confidence: 99%
“…Another group studied 11 pregnant women that also demonstrated significant decreases in the ratio of plasma lamotrigine concentration to dose compared with pre-pregnancy values (51). Five patients in another study experienced seizure deterioration during gestation and there was significant inter-patient variability in the pharmacokinetics of lamotrigine (52).…”
Section: Lamotriginementioning
confidence: 97%
“…9,20 Although there is a lack of data for many of the newer generation antiepileptic drugs, the pharmacokinetics of lamotrigine (Table 2) during pregnancy have been examined by several investigators in recent years. Available studies have consistently reported a marked decline in lamotrigine plasma concentrations during pregnancy, 18,20,[22][23][24][25] most notably later in gestation. 18 It has been hypothesized that the observed changes in plasma levels during pregnancy are due to enhanced elimination by induction of glucuronidation (UGT1A4 18 ) of lamotrigine.…”
Section: Antiepileptic Drugsmentioning
confidence: 98%
“…It has been recommended that plasma lamotrigine levels be monitored at regular intervals during pregnancy (and postpartum) in women with epilepsy. 20,22,24 Whether the benefit of TDM of lamotrigine during pregnancy can be extended to bipolar patients is unclear 21 as therapeutic blood levels are not defined for this condition and dosing is typically determined by clinical response. 11…”
Section: Antiepileptic Drugsmentioning
confidence: 99%